Inflammation and immunity in depression : basic science and clinical applications - Baune, Bernhard T. (Academic Press, an imprint of Elsevier, 2018)
"Inflammation and Immunity in Depression: Basic Science and Clinical Applications is the first book to move beyond the established theory of cytokine-induced depression and explore the broader role the immune system plays in this devastating mood disorder. The book fully explores the most recent lines of research into this rapidly advancing field, including alterations of T-cells, the neurobiological implications of neuroinflammation and immune alterations for brain development and function, and the genetic components of neuroinflammation in depression, including the relationships between stress and inflammation that are revealing gene-environment interactions in the disorder."